IDENTIFIKASI PEPALIHAN BEBADUNGAN PADA GEDONG RATU DALEM DI PURA DALEM TOH JAYA - Wasista, I Putu Udiyana (Studi Budaya Nusantara, 2021)
Bebadungan style preservation is important, because of the large- scale renovation without paying attention to the legacy of knowledge for future generation. In addition, writings that spesifically discussing the various type of pepalihan bebadungan have not been found. This paper contain an identification of the various type of pepalihanbebadungan used in Gedong Ratu Dalem at Pura Dalem Toh Jaya, Banjar Lemintang, Dauh Puri Kaja Village, Denpasar City. This paper used qualitative method with descriptive presentation. This paper aims to documented and contributed to literacy that play a role in cultural preservation at the Denpasar City. The result is that there are 10 different types of pepalihan used, including palih dandan and palih cakep gula that is the spesific characteristics of bebadungan style. The whole things is visualized in a game of linear lines, with variations of bricklaying back and forth to create depth.